Escape Room Interaktif Berbasis Manajemen Penugasan: Solusi Inovatif Untuk Mengatasi Academic Disengagement Siswa Sekolah Dasar - Rafid Fahruddin; Binar Ringga Pura Rakasiwi; Sagita Dewi Anggraini; Dina Lusiana (Nur Science Institute, 2025)
Background: This study aims to examine the effectiviness of using interactive escape room learnig media based on task management in mitigating academic disengagement among elementary school students Method: This research amploys a quantitative approach with a pre-experimental design using a one-group pretest- posttest design. The research subjects were 25 sixth-grade students of SD Parang 2. The insrument used was an academic disengagement questionnaire with a likert scale covering three aspects: behavioral, emotional, and cognitive. The results showed that all items were valid and reliable, with a Cronbach’s Alpha value of 0.0945. the normality test indicated that the data were not normally distrubuted; therefore, the analysis was continued using the nonparametric Mann-Whitney test. Result: The results of this study showed that (1) Most teachers did not observe yet their students inside and outside class activity every day. (2) Some teachers take notes every day, some others incidentally. The indicators got from a combination of official guideline and their own. (3) All teachers at least asses two dimensions (discipline and honesty), the others wholly ignored. All teachers at least use two techniques. (4) The teachers follow up on the assessment by informs students periodically (quarterly) and give them praise or advice. Implication: The hypothesis test results showed a significance value of 0.000 (<0.05), indicating a significant difference between the pretest and posttest. The mean score decreased from 36.90 in the pretest to 14.10 in the posttest. Thus, it can be concluded that the interactive escape room learning media based on. task management is effective in mitigating students’ academic disengagement Novelty: This media is able to enhance students’ engagement behaviorally, emotionally, and cognitively through interactive, structured, and enjoyable learning.